Atypical teratoid/rhabdoid tumors in children treated with multimodal therapies: The necessity of upfront radiotherapy after surgery. Issue 12 (9th June 2017) - Lee, Jeongshim; Kim, Dong‐Seok; Han, Jung Woo; Suh, Chang‐Ok
Abstract: Background: Atypical teratoid/rhabdoid tumor (ATRT) is a rare malignant pediatric brain tumor with a dismal prognosis. We evaluated the efficacy of multimodal therapy in children with ATRT. Procedure: Nine children diagnosed with cranial ATRT, who received multimodal therapy between 2005 and 2014, including surgical resection followed by radiotherapy (RT), systemic chemotherapy (CT), and high‐dose chemotherapy/stem cell transplantation (HDCT/SCT), were analyzed retrospectively. The median age at diagnosis was 32 months. Initial treatment included surgery in eight patients (88%), CT in all (100%), RT in eight (88%), and HDCT/SCT in seven (78%). Results: The median follow‐up period for survivors was 21 months. The 2‐year progression‐free rate was 66.7%. Two patients had progression 4 and 17 months after diagnosis. One received multimodal treatment, including surgery and upfront CT with delayed RT; the other underwent surgery and upfront CT without RT. The 2‐year event‐free survival and overall survival rates were 46.7% and 62.2%, respectively. Hematologic toxicity of grade 3 or more was observed in six patients treated with HDCT/SCT and two who underwent craniospinal irradiation. Deaths were attributed to progressive disease (n = 2) and treatment‐related toxicity (n = 2) from sepsis and acute respiratory failure after CT and HDCT/SCT. Conclusions: Maximal safe resection in conjunction with upfront RT is a reasonable multimodal treatment in patients with ATRT for prolonging progression‐free survival. Further research may help determine the optimal parameters for reducing treatment toxicity, such as intensity of HDCT/SCT and the RT field.